2020
DOI: 10.1101/2020.05.10.20097428
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Will an imperfect vaccine curtail the COVID-19 pandemic in the U.S.?

Abstract: The novel coronavirus (COVID-19) that emerged from Wuhan city of China in late December 2019 continue to pose devastating public health and economic challenges across the world. Although the community-wide implementation of basic non-pharmaceutical intervention measures, such as social-distancing, quarantine of suspected COVID-19 cases, isolation of confirmed cases, use of face masks in public, and contact-tracing, have been quite effective in curtailing and mitigating the burden of the pandemic, it is univers… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 21 publications
5
65
0
Order By: Relevance
“…Based on estimates that vaccination coverage of close to 75% may be required to vaccinate to eradicate coronavirus 4,5,10,26 , our estimates that close to 50% of the population may be willing to vaccinate are concerning. It will now be critical to better understand the reasons why a large proportion of the population are sceptical about vaccination against COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on estimates that vaccination coverage of close to 75% may be required to vaccinate to eradicate coronavirus 4,5,10,26 , our estimates that close to 50% of the population may be willing to vaccinate are concerning. It will now be critical to better understand the reasons why a large proportion of the population are sceptical about vaccination against COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…. Simulation studies suggest at least three quarters of the population may need to be vaccinated to extinguish the ongoing coronavirus pandemic 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Although concerted global efforts are exerted towards developing a safe and effective vaccine against COVID-19 [24] , [25] , [26] , [27] , no such vaccine is expected to be ready for use in humans by September 2020. Furthermore, there is currently no safe and effective antiviral against the virus.…”
Section: Introductionmentioning
confidence: 99%
“…Results indicated that the strategy involving practicing proper coughing etiquette, maintain distancing, covering cough and sneezing with disposable tissues and washing of hands is the most cost-effective strategy. Other mathematical models on COVID-19 with varying mathematical concepts can be found in [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%